The Grassroots of Brick City: A History of Community Organizing for School Reform in Newark, New Jersey, 1960s - 2010s - Fullam, Jordan P. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Newark, New Jersey has been at the forefront of school reform from the civil rights era through more recent efforts to resist neoliberal school reform approaches during the 2010s. Drawing on interviews with activists, policymakers, and school reformers, this paper documents the history of community organizing as a strategy to improve conditions in Newark’s schools. The paper concludes that community organizing in Newark has (1) increased representation for people of color in positions of institutional authority, and (2) achieved intermediate reforms that improved conditions in schools. However, community organizers in Newark have often come up against a power structure that resists broader challenges to class inequality and policymakers that prefer market-based approaches to school reform.